Preference of U.P. clothing technology students on the web site features and services of fashion e-tailers on Multiply. - Velasco, Jill Ann L. (College of Home Economics, University pf the Philippines Diliman, 2010)
This quantitative research identifies the factors that affect the consumer's behavior when shopping online. Also, it determined the preference of B.S. Clothing Technology students from U.P. Diliman on the Web site features and services offered by fashion e-tailers on Multiply. The information would be beneficial for the fashion and retail industry as it can help make the most of the advantages offered by Internet. Using convenience purposive sampling, 44 first to fourth year B.S. Clothing Technology students from U.P. Diliman who were enrolled in CT classes on 2nd semester, 2009-2010 were selected. Only the students who have tried shopping or at least browsing through an online fashion store on Multiply was selected as respondents. Data was gathered through survey questionnaires, The results were analyzed using frequency analysis and factor rating method. Twenty seven most frequented online fashion retails hops on Multiply selected by the respondents were also analyzed. The presence of the features and services on these sites were evaluated. The survey revealed the following results: 1) the primary reason that hinders the students from shopping online is their lack of trust with Web shopping; 2) convenience, variety of choices and accessibility are the most encouraging factors to online shopping; 3) the respondents rely more from the recommendations of people they know when choosing for an online fashion brand on Multiply; 4) students prefer the product worn by a model when presenting the merchandise and fit; 5) the most important information the students look for when shopping online is the price and product description; 6) the respondents find door-to-door the safest and most convenient way of delivering the product; 7) G-cash is the most convenient mode of online payment while bank transfer is the safest; 8) Respondents find personal messaging both the safest and the most convenient way of communicating with the seller. Findings also show that the features and services the respondents prefer are all present in the online fashion stores that they frequent. This study therefore, recommends the use of the features and services that the consumers prefer to promote their online stores. Further studies could use a larger sample unit and the use of qualitative data to broaden the study. Also, this could help identify new shopping behavior models. The effectiveness of the features and services in promoting sales could also be included in future research.